Prevalence of peptic ulcer in Helicobacter pylori positive blood donors. Issue 3 (March 1994) - Vaira, D; Miglioli, M; Mulè, P; Holton, J; Menegatti, M; Vergura, M; Biasco, G; Conte, R; Logan, R P; Barbara, L
Abstract : This study aimed to determine the importance of raised antibodies to Helicobacter pylori in an asymptomatic population. A total of 128 asymptomatic blood donors who were seropositive for H pylori and consented to endoscopy were investigated. These subjects were from a population of 1010 blood donors screened for antibodies to H pylori. A questionnaire was completed to determine if any subjects had complained of symptoms, and they subsequently had endoscopy. Altogether 121 of 128 were positive for H pylori by histology and urease test and/or culture and all 121 had chronic active gastritis on histology. Twenty five of these subjects had peptic ulcer (20 duodenal, five gastric), a further 21 had erosive duodenitis, and two were found to have gastric cancer. H pylori associated peptic ulcer disease and duodenitis occur more frequently than previously recognised and this suggests that H pylori infection, even if asymptomatic, is of far greater clinical relevance than originally thought.